Political communication strategy of Sahabat Ganjar Pranowo (SAGA) in increasing electability ahead of the presidential elections of the Republic of Indonesia - Rosy Febriani Daud (Department of Communication Studies, Faculty of Social and Political Sciences Universitas, 2023)
The Lampung Ganjar's Friends Volunteer (SAGA) conducts personal branding to increase the electability of the Candidate for the President of the Republic of Indonesia, Ganjar Pranowo. The personal branding aims to shape the public's perception of Ganjar Pranowo's personality, making it easier for the Lampung SaGa volunteers to implement political communication strategies. The political communication strategies are employed to facilitate two-way communication with the public and establish a distinct character, shaping the self-image, and enhancing electability. This research explores the political communication strategies utilized by the Lampung Ganjar's Friends Volunteer (SAGA) in boosting electability ahead of the Presidential election in Indonesia. The method employed in this study is a qualitative descriptive approach. The research findings are as follows: Firstly, the volunteers observe the issues before devising political communication strategies. They analyze the situation thoroughly. Secondly, the Lampung Ganjar's Friends Volunteer (SAGA) manages the planning and program development. They create a detailed action plan. Thirdly, the communication actions are taken, and the planned programs are implemented efficiently, focusing on designing Ganjar Pranowo's personal image (Personal Branding) as effectively as possible. Fourthly, program evaluation is conducted, during which the Lampung Ganjar's Friends Volunteer (SAGA) can assess the activities' success and achievements.